(untitled) (International Journal of Engineering and Computer Science, 2015)
Multipath routing protocol is the most important aspect of Ad-Hoc network, the performance of Ad-hoc network mainly depends on routing protocol this paper address the problem of existing multipath routing protocol and also discussed the new routing protocol namely IPL_AOMDV, and also compare them in terms of Load balance, congestion control and power control parameter and found that IPL_AOMDV outperform the existing routing protocol in each aspect.